Acid Additives Enhancing the Conductivity of Spiro‐OMeTAD Toward High‐Efficiency and Hysteresis‐Less Planar Perovskite Solar Cells. Issue 4 (28th October 2016) - Li, Zhen; Tinkham, Jonathan; Schulz, Philip; Yang, Mengjin; Kim, Dong Hoe; Berry, Joseph; Sellinger, Alan; Zhu, Kai
Abstract : A general doping strategy, using a wide range of acids with different p Ka values as additive, is demonstrated to enhance the conductivity of spiro‐OMeTAD, the dominant hole transport material in perovskite solar cells (PSCs). Hysteresis‐less planar PSCs with ≈19% efficiency and better open‐circuit voltage and fill factor is achieved with acid doped spiro‐OMeTAD.